Analisis Literatur Tentang Radiasi Termal Dalam Astrofisika - Sarumaha, Enjellyn; Harefa, Candra Ponus (CV. SINAR HOWUHOWU, 2025)
Thermal radiation is a fundamental phenomenon in astrophysics that plays a key role in understanding various astronomical objects and cosmic processes. In the context of astrophysics, thermal radiation is produced by celestial objects that have temperatures above absolute zero, such as stars, planets, and nebulae. The Stefan-Boltzmann Law and Wien's Law are important tools for characterizing the spectrum of radiation emitted by these objects, which depends on their temperature and material properties. The study of thermal radiation allows astronomers to estimate the temperature, chemical composition, and distance of celestial objects. For example, analysis of the spectrum of thermal radiation from stars provides information about their evolutionary stage and formation mechanisms. In addition, thermal radiation from galaxies and star clusters provides insight into the history of the formation of structures in the universe. This article reviews the basic mechanisms of thermal radiation, its applications in astronomical observations, and its impact on our understanding of cosmic evolution. With advances in telescope technology and remote sensing instruments, the study of thermal radiation will continue to make significant contributions to the exploration and understanding of the universe.